2018
DOI: 10.5761/atcs.oa.17-00102
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Pulmonary Edema after Minimally Invasive Cardiac Surgery with Mini-Thoracotomy Using Neutrophil Elastase Inhibitor

Abstract: Purpose: Unilateral re-expansion pulmonary edema (RPE) is a rare but one of the most critical complications that may occur after re-expansion of a collapsed lung after minimally invasive cardiac surgery (MICS) with mini-thoracotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The incidence varies from study to study. The reported incidence of radiographically evident UPE after MICS was 5.0%-7.9%, and that of symptomatic UPE after MICS was reported to be 1.5% or "rare" [1,2]. As the number of MICS procedures has increased, reports related to UPE after MICS have increased as well.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence varies from study to study. The reported incidence of radiographically evident UPE after MICS was 5.0%-7.9%, and that of symptomatic UPE after MICS was reported to be 1.5% or "rare" [1,2]. As the number of MICS procedures has increased, reports related to UPE after MICS have increased as well.…”
Section: Discussionmentioning
confidence: 99%
“…A number of inflammatory factors are involved in the damage to the lungs and other important organs after CPB [ 22 , 23 ]. Evidence shows that neutrophils are closely related to the degree of lung injury and the levels of inflammatory factors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…17) Recently, sivelestat was also reported to exert protective effects against re-expansion pulmonary edema, which is one of the crucial complications that occurs after minimal invasive cardiac surgery with minithoracotomy. 18) Most clinical studies have demonstrated that sivelestat attenuates lung injury or improves pulmonary dysfunction; however, Toyama et al showed that it improves not only the respiratory index but also changes in the fractional area of the left ventricle during pediatric cardiovascular surgery with cardiopulmonary bypass. 17) Consistently, the present study demonstrated an improvement in both LV function and endothelial function after cardioplegic arrest when sivelestat was administered during the first 10 min of reperfusion in isolated Langendorff-perfused rat hearts.…”
Section: Discussionmentioning
confidence: 99%